Analyst Audited Financial Statements of Baznas Cirebon City - Ahdi, Makmuri (Jurnal Ekonomi : Journal of Economic, 2026)
The purpose of this study is to analyze the Audited Financial Statements of the National Amil Zakat Agency (BAZNAS) of Cirebon City for 2019-2020 using the Allocation to Collection Ratio (ACR), the ratio of operational costs, and the growth ratio. The research method used is descriptive analysis with a quantitative approach. The results of this study indicate that based on the Allocation to collection ratio (ACR), the activity performance of the Cirebon City National Amil Zakat Agency (BAZNAS) in 2019-2020 is effective, except for the Gross Allocation to Collection Ratio in 2019 which is not effective. Based on the operational cost ratio, management performance in using the Cirebon City National Amil Zakat Agency (BAZNAS) operational costs in 2019-2020 is inefficient. Meanwhile, based on the growth ratio, there was an increase in positive growth in collection growth, distribution growth, and growth in operating costs. This is an indicator that the trust of muzak to entrust zakat, infaq, and alms funds to the National Amil Zakat Agency (BAZNAS) of Cirebon City is increasing.